cos^2x+sin^2x+2sinxcosx=cos^2x-sin^2x
2sinxcosx+2sin^2x=0
sinxcos+sin^2x=0
sinx(cosx+1)=0
sinx=0 x=Пk
cosx=-1
x=-П+2Пk
sqrt( -3x^2-8x+11(x+2)(10-x))=sqrt(-3x^2-8x-11(x^2-8x-20))=sqrt(-3x^2-8x-11x^2+88x+220)=sqrt(-14x^2+80x+220)
14x^2-80x-220<0
7x^2-40x-110<0
если только правильно была понята запись примера
1. cos x^2 + 2sinxcosx + sinx^2 - cosx^2 +sinx^2 = 0
2sinx^2 + 2sinxcosx = 0
sinx(1+cosx) = 0
sinx = 0 cosx = -1
x = Пn, n принадлежит Z x = П + 2Пk, k принадлежит Z
cos^2x+sin^2x+2sinxcosx=cos^2x-sin^2x
2sinxcosx+2sin^2x=0
sinxcos+sin^2x=0
sinx(cosx+1)=0
sinx=0 x=Пk
cosx=-1
x=-П+2Пk
sqrt( -3x^2-8x+11(x+2)(10-x))=sqrt(-3x^2-8x-11(x^2-8x-20))=sqrt(-3x^2-8x-11x^2+88x+220)=sqrt(-14x^2+80x+220)
14x^2-80x-220<0
7x^2-40x-110<0
если только правильно была понята запись примера
1. cos x^2 + 2sinxcosx + sinx^2 - cosx^2 +sinx^2 = 0
2sinx^2 + 2sinxcosx = 0
sinx(1+cosx) = 0
sinx = 0 cosx = -1
x = Пn, n принадлежит Z x = П + 2Пk, k принадлежит Z